Chlamydia trachomatis targets mitochondrial dynamics to promote intracellular survival and proliferation. (30th October 2018) - Kurihara, Yusuke; Itoh, Ryota; Shimizu, Akinori; Walenna, Nirwana Fitriani; Chou, Bin; Ishii, Kazunari; Soejima, Toshinori; Fujikane, Aya; Hiromatsu, Kenji
Abstract: Chlamydia trachomatis is an obligate intracellular bacterium that scavenges host metabolic products for its replication. Mitochondria are the power plants of eukaryotic cells and provide most of the cellular ATP via oxidative phosphorylation. Several intracellular pathogens target mitochondria as part of their obligatory cellular reprogramming. This study was designed to analyse the mitochondrial morphological changes in response to C .  trachomatis infection in HeLa cells. Mitochondrial elongation and fragmentation were found at the early stages and late stages of C .  trachomatis infection, respectively. C .  trachomatis infection‐induced mitochondrial elongation was associated with the increase of mitochondrial respiratory activity, ATP production, and intracellular growth of C .  trachomatis . Silencing mitochondrial fusion mediator proteins abrogated the C .  trachomatis infection‐induced elevation in the oxygen consumption rate and attenuated chlamydial proliferation. Mechanistically, C .  trachomatis induced the elevation of intracellular cAMP at the early phase of infection, followed by the phosphorylation of fission‐inactive serine residue 637 (S637) of Drp1, resulting in mitochondrial elongation. Accordingly, treatment with adenylate cyclase inhibitor diminished mitochondrial elongation and bacterial growth in infected cells. Collectively, these results strongly indicate that C .  trachomatis promotes its intracellular growth by targeting mitochondrial dynamics to regulate ATP synthesis via inhibition of the fission mediator Drp1.